The need for acute assessments in home healthcare - Swedish registered nurses’ experiences - Jessica Westerholm; Lena-Karin Gustafsson; Mirkka Söderman (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The study aims to describe Swedish RNs’ experiences of acute assessments at home. More patients with complex nursing needs are cared for at home due to an ageing population. Registered nurses (RNs) who work with home healthcare need a broad medical competence and clinical experience alongside adapted decision support systems for maintaining patient safety in acute assessments within home healthcare. Methods A content analysis of qualitative survey data from RNs (n = 19) working within home healthcare in Sweden. Results There were challenges in the acute assessments at home due to a lack of competence since several of the RNs did not have much experience working as an RN in home healthcare. Important information was missing about the patients, such as access to medical records due to organizational challenges and limited access to equipment and materials. The RNs needed support in the form of cooperation with a physician, support from colleagues, and a decision support system. Conclusion To increase the possibility of patient-safe assessments at home, skills development, collegial support, and an adapted decision support system are needed. Collaboration with primary healthcare, on-call physicians, and nursing staff, and having the opportunity to consult with someone also provide security in acute assessments.